Efectos de la raza y el sexo en el logro educativo y estatus ocupacional en el primer empleo en la ciudad de Cali Colombia - Viáfara López, Carlos Augusto (Sociedad y Economía, 2006)
This article values the importance of social origins and individual achievement in the social stratification process of racial groups in the city of Cali. This work is based on the biographical sample of the CIDSE-IRD survey, carried out in Cali in 1998. The findings suggest that the much lower outcomes obtained by black individuals in the process of social stratification have been produced not only because they have poorer parents and less education, but also because of the presence of cumulative disadvantages along the life course that could be interpreted as racial and sexual discrimination.